A priori power considerations in orthodontic research: a 3 year meta-epidemiologic study. (15th August 2019) - Gratsia, Sophia; Koletsi, Despina; Fleming, Padhraig S; Pandis, Nikolaos
Summary: Aim: To assess the prevalence of a priori power calculations in orthodontic literature and to identify potential associations with a number of study characteristics, including journal, year of publication and statistical significance of the outcome. Materials and methods: The electronic archives of four leading orthodontic journals with the highest impact factor ( American Journal of Orthodontics and Dentofacial Orthopedics, AJODO; European Journal of Orthodontics, EJO; Angle Orthodontist, ANGLE; Orthodontics and Craniofacial Research, OCR) were assessed over a 3 year period until December 2018. The proportion of articles reporting a priori power calculations were recorded, and the association with journal, year of publication, study design, continent of authorship, number of centres and researchers, statistical significance of results and reporting of confidence intervals (CIs) was assessed. Univariable and multivariable regression were used to identify significant predictors. Results: Overall, 654 eligible articles were retrieved, with the majority published in the AJODO ( n = 246, 37.6%), followed by ANGLE ( n = 222, 33.9%) and EJO ( n = 139, 21.3%). A total of 233 studies (35.6%) presented power considerations a priori along with sample size calculations. Study design was a very strong predictor with interventional design presenting 3.02 times higher odds for a priori power assumptions compared to observational research [odds ratio (OR): 3.02; 95% CIs: 2.06, 4.42; P < 0.001]. Conclusions: Presentation of a priori power considerations for sample size calculations was not universal in contemporary orthodontic literature, while specific study designs such as observational or animal and in vitro studies were less likely to report such considerations.